Telling the Land: Aboriginal Educational Narratives and Curriculum Integration in Australian Schools - Oliver Harris; Sarah Taylor; Thomas Mitchell (Yayasan Adra Karima Hubbi, 2025)
Background. Efforts to meaningfully integrate Aboriginal perspectives into Australian school curricula remain uneven and contested, often constrained by systemic limitations and a lack of culturally informed pedagogical frameworks. Aboriginal narratives, particularly those tied to Country, embody holistic systems of knowledge that challenge Western linear constructions of curriculum and offer alternative modes of understanding land, identity, and education. Purpose. This study explores how Aboriginal educational narratives are interpreted and integrated into curriculum practice by both Indigenous and non-Indigenous educators across diverse Australian school settings. Method. Employing a qualitative, multi-site case study approach, the research involved interviews with 22 educators and curriculum leaders, alongside analysis of classroom materials and reflective teaching journals. Results. The findings reveal that successful integration depends on deep, relational engagement with community knowledge holders, an ethic of cultural humility, and a willingness to reconfigure disciplinary boundaries. Educators who engaged in collaborative curriculum-making reported greater confidence in embedding Indigenous perspectives in ways that respect narrative sovereignty and pedagogical integrity. Conclusion. The study concludes that Aboriginal storytelling offers not only content but a methodtransforming curriculum into a site of shared responsibility, ethical dialogue, and place-based learning.